Interactive world issues of place and planet (McGraw Hill Higher Education, 2004)
Περίληψη από το κιβώτιο: "McGraw-Hill and Cambridge Studios have partnered to create an exciting study tool that captures the power of media to allow you and your students to visit different world regions and explore geographic and environmental issues. Each case study features high quality videos, animations, maps, and diagrams as interactivities that students can complete as assignments or self-paced study. The case studies address relevant events and issues such as resource allocation, land reform, water rights, policy, economic conditions, population, and sustainability."